A Framework Analysis of Digital Transformation: Insights from the Romanian National Recovery and Resilience Plan - Laura-Elena Marinaș; Alina-Camelia Belciu (Vasilescu); Elena-Simona Ionel (Romanian Journal of European Affairs)
The aim of this paper is to examine the digital transformation (DT) framework embedded in the Romanian National Recovery and Resilience Plan (NRRP). We employed a combination of research methods to achieve the objectives of this paper. We depict and analyse the logic of the NRRP in relation to the DT framework derived from scholarly literature, the European Union’s (EU) Digital Decade, and the priorities and targets of the Recovery and Resilience Facility (RRF). Despite the fact that reforms and investments aligned with EU’s priority policy areas are structured around a catch-up approach, the NRRP plays a crucial role as a catalyst for a comprehensive and coherent digitalisation strategy. We conclude that the NRRP not only functions as a funding instrument, but also plays a pivotal role in shaping Romania’s strategic framework for DT.